2021
DOI: 10.21977/d916145329
|View full text |Cite
|
Sign up to set email alerts
|

It got me back to science and now I want to be a plant scientist: Arts-integrated science engagement for middle school girls

Abstract: While middle school is a critical phase for science career development for all students (Maltese & Tai, 2009), this stage presents considerations for females in science, in particular. During middle school, the decline in science interest is greater for females than males and, for most students, the level of science interest developed during this middle school stage will persist throughout their lifetime, thereby influencing science career interests and supported the research study by co-developing and enactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…There is no additional cost, as all you need is paper and pencil. It can, however, support motivation to learn (Mark et al, 2020), as the interviewees' experiences suggest. In common with Peppler et al (2014), this study found that sketch noting encourages interaction and collaboration between students.…”
mentioning
confidence: 99%
“…There is no additional cost, as all you need is paper and pencil. It can, however, support motivation to learn (Mark et al, 2020), as the interviewees' experiences suggest. In common with Peppler et al (2014), this study found that sketch noting encourages interaction and collaboration between students.…”
mentioning
confidence: 99%